Management of Bleeding Associated with New Oral Anticoagulants - Franchini, Massimo; Bonfanti, Carlo; Mannucci, Pier Mannuccio (Seminars in Thrombosis and Hemostasis, 2015)
In the last few years, a great improvement in the management of clinical thromboembolism has been made thanks to the availability of novel oral anticoagulants. These drugs, which act by directly inhibiting thrombin (dabigatran) or activated factor X (apixaban, rivaroxaban, and edoxaban), offer several practical advantages over the traditional vitamin K antagonists (VKA), such as a more predictable anticoagulant effect with no need for routine coagulation monitoring and a limited drug and food interaction. Several phase III clinical trials have now been completed, overall demonstrating that non-VKA oral antagonists (NOACs) are at least as efficacious and safe as VKA in the prevention and treatment of thromboembolism. Nevertheless, patients receiving NOACs represent a new challenge because no antidotes are currently available for these drugs. In this review, after a description of the main pharmacologic characteristics and the main results of the clinical trials of NOACs, we will focus on the management of bleeding associated with these anticoagulant agents. A treatment algorithm of NOACs-associated bleeding is finally provided, with the aim of helping physicians in their daily care activity.
Keywords: new oral anticoagulants; dabigatran; apixaban; rivaroxaban; edoxaban; bleeding; antidote